Tubular MYDGF Slows Progression of Chronic Kidney Disease by Maintaining Mitochondrial Homeostasis - Xiaohan Liu; Yang Zhang; Youzhao Wang; Yujie Yang; Zhe Qiao; Ping Zhan; Huiying Jin; Qianqian Xu; Wei Tang; Yu Sun; Yan Zhang; Fan Yi; et al. (Advanced Science)
Abstract Mitochondrial dysfunction is a key event driving the maladaptive repair of tubular epithelial cells during the transition from acute kidney injury to chronic kidney disease (CKD). Therefore, identifying potential targets involved in mitochondrial dysfunction in tubular epithelial cells is clinically important. Myeloid‐derived growth factor (MYDGF), a novel secreted protein, plays important roles in multiple cardiovascular diseases, but the function of MYDGF in tubular epithelial cells remains unknown. In the present study, it is found that MYDGF expression is significantly reduced in the cortex of the kidney, especially in the proximal tubules, from mice with CKD. Notably, lower expression of MYDGF is observed in tubules from patients with CKD and the level of MYDGF correlated with key factors related to kidney fibrosis and estimated glomerular filtration rate (eGFR) in patients with CKD. Tubule‐specific deletion of Mydgf exacerbates kidney injury in mice with CKD; however, Mydgf overexpression attenuates kidney fibrosis by remodeling mitochondrial homeostasis in tubular epithelial cells. Mechanistically, renal tubular MYDGF positively regulates the expression of isocitrate dehydrogenase 2 (IDH2), restores mitochondrial homeostasis, and slows CKD progression. Thus, this study indicates that MYDGF derived from tubules may be an effective therapeutic strategy for patients with CKD.